HUBUNGAN TINGKAT STRES, ASUPAN NATRIUM, DAN RIWAYAT MAKAN DENGAN KEJADIAN STROKE - Puspita Ayu Ramadhani; Merryana Adriani (Universitas Airlangga, 2015)
Stroke is a condition of the local neurological disorder that occurs suddenly, causing blood supply into the brain tissue stop and also causing impaired brain function. There are many causal factors that lead to stroke such as age, stress, natrium consumption, and food history. This study aims to analyze the relation between stress level, natrium consumption, and food history with the incidence of stroke in among stroke outpatients aged ≥ 45 years. This is an analytic observational study using case control design in Neural Poly of Airlangga University Hospital. The population of case group was stroke outpatients aged ≥ 45 years while control group was outpatients aged ≥ 45 years who didn’t have stroke. The sample was 11 patients for each group and were taken using simple random sampling technique. Relation among variables were analyzed using Chi-Square test. The result of this study showed that there is signiﬁ cant relation between natrium consumption level (p = 0,032; OR = 0,083) and food history (p = 0,003; OR = 45,000) with the incidence of stroke. There is no signiﬁ cant relation between stress level (p = 1,000) with the incidence of stroke. It is necessary to give the information about natrium food source and healthy diet in order to prevent the occurrence of stroke.Keywords: natrium, food history, stress, stroke